ETHNOMATHEMATICS EXPLORATION OF TWO-DIMENSIONAL PLANE FIGURES IN TUATUNU GRAND MASJID: INTEGRATING GEOMETRY INTO MATHEMATICS EDUCATION - Fahlevi, Mahfudz Reza; Lubis, Riyani Fitri (Jurnal Pendidikan Matematika dan IPA, 2025)
This research project was conducted to investigate the mathematical aspects, specifically focusing on two-dimensional geometry concepts found in the architectural design of the Tuatunu Grand Masjid, which aimed to integrate these research findings into the mathematics education curriculum. Utilizing a descriptive qualitative methodology from an ethnographic standpoint, information was collected through interviews with two takmir (masjid administrators), as well as through direct observation and documentation. The primary data collection method was direct interaction with participants, which could benefit from further explanation to clarify the specific types of interactions conducted. The analysis process followed Spradley"™s framework, encompassing domain analysis, taxonomy, componential analysis, and identification of cultural themes. The study"™s outcomes highlighted the presence of a variety of geometric shapes within the Tuatunu Grand Masjid, including triangles, quadrilaterals, pentagons, polygons, and circles. These findings suggest that the masjid can serve as a valuable resource for developing educational materials, including worksheets and textbooks, that are grounded in ethnomathematics. By incorporating the architectural features of the masjid into mathematics education, educators can offer students a tangible and practical context for learning two-dimensional geometry, enhancing their understanding and engagement with the subject matter.